PEDAGOGICAL PORTRAIT OF KYIV COLLEGE STUDENT OF THE EARLY TWENTIETH CENTURY AS REFLECTED BY BEHAVIOUR LISTS - Mikhno, Oleksandr (The Modern Higher Education Review, 2017)
This article presents a generalized pedagogical portrait of Kyiv college student of the early twentieth century. The main source of research is students’ behaviour lists of Pavel Galagan College that are stored in the Kyiv State Archives. It was found that behaviour lists is a form of student pedagogical characteristic in the early twentieth century. It is proved that pedagogical characteristics of that time did not have a welldefined structure and they were composed in an arbitrary manner at the end of the school year. Typically, the characteristics were very concise and comprised the following information: level of abilities, behavior, attitude towards others, hobbies, main traits of character. The main value of these characteristics is that the information given in them show a “common” student of the last century. The author of the analysis applies microhistorical approach, manifested in the focus of research interest on “a common man” – a student – and manifested as well in experimental form of presentation of research results that has a form of a dialogue between a reader and a historian. The article also offers a summary of application of microhistorical approach to Ukrainian research on history of education.